CODE MIXING USED BY ONE-PIECE ANIME LOVERS ON SOCIAL MEDIA COMMENTS - Karimah, Syahadah Albaqiyatul (Metahumaniora, 2024)
Code mixing is a common practice in communication both in formal or informal situations. The use of code mixing is not only limited to everyday oral conversations, nowadays, code mixing can also be found in posts of comments on social media. The study analyses the code mixing used by One Piece anime lovers on social media. This is a descriptive quantitative study gathered data from the comments uploaded by the anime lovers on social media namely YouTube, Instagram, and TikTok. The data gathered were analysed by using Muysken’s theory (2000) for the types of code-mixing and Hoffman’s theory (1991) for the reasons of code mixing. The results showed that in the One-Piece anime lovers’ community on social media, the most dominant type of code mixing used is insertion and the reasons for using code mixing are to talk about particular topic and creating familiar interactions in conversations only. Social factors that influence the use of code mixing include fan age demographics, trends, and language style. In addition, code mixing is also used to facilitate the understanding of a word context.